Does stewardship theory provide a viable alternative to control-fixated performance management? - Jacob Torfing; Tina Øllgaard Bentzen (Administrative Sciences, 2020)
Stewardship theory provides an interesting alternative to agency theory, which in the recent New Public Management era supported the introduction of rigorous performance management systems based on generalized mistrust in and control of public employees. However, we lack empirical validation of the feasibility and positive outcomes of the new forms of trust-based management recommended by stewardship theory. As such, there are few examples of alternative ways of boosting the motivation of public employees that can serve as beacons for public service organizations (PSOs) eager to find new ways of motivating their staff to create public value for the users of public services and society as a whole. This article aims to remedy this problem by exploring a seemingly successful empirical case of trust-based management to see whether the core principles of stewardship theory apply and how new management practices may influence the motivation and well-being of the employees, the perceived satisfaction and involvement of the users, and overall organizational performance, including cost efficiency.
Keywords: 350; agency problem; stewardship; performance management; public service organizations; public service motivation; intrinsic task motivation